2020
DOI: 10.1038/s41598-020-64568-2
|View full text |Cite
|
Sign up to set email alerts
|

Niche shifts and environmental non-equilibrium undermine the usefulness of ecological niche models for invasion risk assessments

Abstract: niche shifts and environmental non-equilibrium in invading alien species undermine niche-based predictions of alien species' potential distributions and, consequently, their usefulness for invasion risk assessments. Here, we compared the realized climatic niches of four alien amphibian species (Hylarana erythraea, Rhinella marina, Hoplobatrachus rugulosus, and Kaloula pulchra) in their native and Philippine-invaded ranges to investigate niche changes that have unfolded during their invasion and, with this, ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 92 publications
(122 reference statements)
7
67
0
Order By: Relevance
“…Unfilling is thought to result from a lag between colonization and range expansion (Petitpierre et al., 2012), so it is unsurprising that niche contractions in climatic space corresponded to predictions of lesser geographic spread, particularly in introduced species. Our study provides further support (Camenen et al., 2016; Li et al., 2014; C. Liu et al., 2020; Strubbe et al., 2013) for the hypothesis that niche dynamics in introduced species are dominated by unfilling (Petitpierre et al., 2012; VĂĄclavĂ­k & Meentemeyer, 2012), and that this is borne out in geographic models (but see Early & Sax, 2014; Pili et al., 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Unfilling is thought to result from a lag between colonization and range expansion (Petitpierre et al., 2012), so it is unsurprising that niche contractions in climatic space corresponded to predictions of lesser geographic spread, particularly in introduced species. Our study provides further support (Camenen et al., 2016; Li et al., 2014; C. Liu et al., 2020; Strubbe et al., 2013) for the hypothesis that niche dynamics in introduced species are dominated by unfilling (Petitpierre et al., 2012; VĂĄclavĂ­k & Meentemeyer, 2012), and that this is borne out in geographic models (but see Early & Sax, 2014; Pili et al., 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Many studies have used SDMs to predict potentially suitable areas for invasive species 45 . However, if niche shifts occur during invasion, be they realized or fundamental niche shifts, these SDM predictions will not be reliable 46 . But for invasion biologists, it is encouraging that the most invasive species showed the smallest niche shifts, indicating that SDM predictions or climate-matching risk assessments for species which pose the greatest environmental risks may be the most reliable.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of CWD in Virginia, our jackknife analysis identified that every CWD case influences the amount of risk predicted. Hypervolumes never reaching a complete overlap (i.e., a Jaccard index value of 1) could suggest that variation seen in environmental space with new CWD cases could stem from disease non-equilibrium, meaning CWD current distribution may not be exhausting its potential occupancy of environmental conditions (74). Under this finer-population scale, this would not be surprising given what is known about nearby CWD cases outside of Virginia withheld from this analysis, the range of landscape conditions that CWD has been identified worldwide (e.g., Scandinavia) (75), and the environmental hardiness of prions in general.…”
Section: Discussionmentioning
confidence: 99%